Fig Psyllid Homotoma ficus (L.) (Insecta: Hemiptera: Homotomidae); Curtain Fig Psyllid Macrohomotoma gladiata Kuwayama (Insecta: Hemiptera: Homotomidae); and Ficus Leaf-Rolling Psyllid Trioza brevigenae Mathur (Insecta: Hemiptera: Triozidae) - Alexander Tasi; Susan Halbert; Tolulope Morawo (EDIS, 2021)
This article details three adventive (to North America) psyllid species that feed on ficus. Homotoma ficus (the fig psylla) was noticed first in 1969, and Macrohomotoma gladiata (the curtain fig psyllid) and Trioza brevigenae (the ficus leaf rolling psyllid) were found to be present in 2015 and 2016, respectively. All three three species are currently found only in California, but could possibly spread to other states including Florida in the future.